The Effectiveness of Using Artificial Intelligence (AI) in Basic Programming Courses in the Mathematics Education Study Program at Mataram University - Gilang Primajati; M. Gunawan Supiarmo; Dita Oktavihari (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The integration of AI in various fields is essential today, including education. The learning process in programming courses, which are often considered challenging, has found new insights through the use of AI. This study aims to analyze the effectiveness of using Artificial Intelligence (AI) in supporting the learning process of the Basic Programming course in the Mathematics Education Program at Mataram University. Using a quantitative approach and a quasi-experimental design, this study compares the learning outcomes of students who use AI assistance in the form of ChatGPT and Deepseek with those who use conventional methods. The results of the study indicate that AI enhances conceptual understanding, task completion efficiency, and student motivation. Thus, the integration of AI in teaching basic programming has proven to be effective and worthy of widespread implementation.